Dragon and Griffin Iconography: Same Origin, Different Destiny - Arroyo Cuadra, Sara (Eikón / Imago, 2012)
Bestiaries are one of the main iconographic sources for medieval art comprehension. Text and image are joined in these sources and they were aimed at materializing and explaining abstract ideas through animal behavior, ideas which were Christianized to transfer a moral education according to ecclesiastical principles. Among those animals are included the dragon and the griffin, beings whose origin was probably shared inside Mesopotamian culture, but beings which, after the establishment of their particular iconography, went by different ways, although always sharing their function as treasure guardians too. And it only happened because of development of both images since a symbolic thought attached to the religious interpretation of the surrounding world by human beings in primeval urban cultures.